PENGENALAN SUARA MANUSIA MENGGUNAKAN JARINGAN SYARAF TIRUAN DENGAN METODE LINEAR PREDICTIVE CODING DAN FAST FOURIR TRANSFORM - Nirwan Sinuhaji; Benar; Romulo P. Aritonang (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The voice of each person is basically different from one another, therefore voice can be used in digital technology or biometric methods used by humans to identify or certify a person's identity based on their physical characteristics or behavior and this technology is widely used in the fields of security. Health and finance. The voice identification process is the process of finding out the identity of a person from the voice they speak. The voice verification process is the process of matching the inputted voice with the voice in the database. This study will use an artificial neural network using the linear predictive coding and fast methods as an initial processor. The voice signal obtained from the recording results is processed by a computer with the FFT algorithm so that a digital signal is obtained, then parsed, the results of the feature extraction with the FFT method then become the input of the LPC method and then implemented into the Artificial Neural Network.